DIRECTIONS FOR THE USE OF BIG DATA AND ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN INSURANCE INSTITUTIONS (E Global Congress, 2026)
This study explores the key directions for applying Big Data and artificial intelligence in insurance institutions. It highlights their role in improving risk assessment, operational efficiency, and customer-oriented services.